Bio-based and bio-inspired adhesives from animals and plants for biomedical applications. (January 2022) - Lutz, Theresa M.; Kimna, Ceren; Casini, Angela; Lieleg, Oliver
Abstract: With the "many-headed" slime mold Physarum polycelphalum having been voted the unicellular organism of the year 2021 by the German Society of Protozoology, we are reminded that a large part of nature's huge variety of life forms is easily overlooked – both by the general public and researchers alike. Indeed, whereas several animals such as mussels or spiders have already inspired many scientists to create novel materials with glue-like properties, there is much more to discover in the flora and fauna. Here, we provide an overview of naturally occurring slimy substances with adhesive properties and categorize them in terms of the main chemical motifs that convey their stickiness, i.e., carbohydrate-, protein-, and glycoprotein-based biological glues. Furthermore, we highlight selected recent developments in the area of material design and functionalization that aim at making use of such biological compounds for novel applications in medicine – either by conjugating adhesive motifs found in nature to biological or synthetic macromolecules or by synthetically creating (multi-)functional materials, which combine adhesive properties with additional, problem-specific (and sometimes tunable) features. Graphical abstract: Image 1